Necropsies of Reptiles: Recommendations and Techniques for Examining Invasive Species - Seth C. Farris; Michiko A. Squires; Frank Ridgley; Emma Lavergne; Mitchell Serota; Frank J. Mazzotti (EDIS)
Captures and postmortem examinations, or necropsies, of invasive or nonnative animals may provide insight into the ecological impact of these invaders. Researchers should be able to perform necropsies when an opportunity arises to examine nonnative species for study. While the techniques described serve as a guide to necropsy of all reptiles, we focus on exotic species found in south Florida. South Florida provides prime habitat for invasive reptiles such as Argentine black and white tegu and Burmese python, and these species are used to describe our techniques. This 26-page fact sheet was written by Seth C. Farris, Michiko A. Squires, Frank Ridgley, Emma Lavergne, Mitchell Serota, and Frank J. Mazzotti, and published by the UF Department of Wildlife Ecology and Conservation, September 2013. http://edis.ifas.ufl.edu/uw382